The Effect of Mobile Seamless Based on Multicultural Education Towards The Enhancement of Learning Outcomes Moderated by Academic Self-Efficacy - Bety Diana Serly Hetharion (JETL (Journal of Education, Teaching and Learning), 2022)
Learning outcomes have an important role in the learning process. But nowadays, being proficient in theory and getting good learning outcomes is not the only goal of Education to be achieved. In the learning process also requires students to be able to give respect and appreciation for human dignity. In this 21st century, it is time for students to be allowed to choose their way and style of learning, where students can determine when and where they will study. Thus, this study is here to determine the effect of seamless learning based on multicultural education on learning outcomes moderated by academic self-efficacy. This research is experimental quantitative research. The population in this study is all students of SMP Kristen Anugerah Kei Kecil. The sample in this study is selected using a clustered sampling technique in which certain groups that already exist in a population are selected as samples. The data in this study are obtained from a questionnaire using a Likert scale. The data in this study are then analyzed in several stages. Based on the results of hypothesis testing, it is known that academic self-efficacy is able to moderate the implementation of seamless learning based on multicultural education on student learning outcomes. Students, teachers, and parents must start adapting online learning tools in order to be able to get more knowledge and sources of information besides, in habituation and daily learning teachers and parents also need to introduce students to diversity so that students understand the value of tolerance.